Social Cognition in Patients With Hypothalamic-Pituitary Tumors - Özyurt, Jale; Mehren, Aylin; Boekhoff, Svenja; Müller, Hermann L.; Thiel, Christiane M. (Frontiers in Oncology, 2020)
Objectives. The current study aimed to investigate whether childhood-onset craniopharyngioma patients are impaired in social-cognitive skills, and whether individual differences in task performance are modulated by the neurohormone oxytocin. Study design. We tested 31 adamantinomatous craniopharyngioma patients with and without hypothalamic lesions and 35 age- and gender-matched healthy controls. To test for between-group differences in social-cognitive skills, we experimentally assessed participants’ abilities to interpret social signs or dispositions and to understand others’ thoughts, feelings, and intentions. Associations between fasting oxytocin saliva concentrations and task performance were analysed across the whole group of participants. Results. Compared to controls, patients with hypothalamic lesions were significantly less able to identify the correct emotional content of vocal expressions and to understand others’ mental states. Judgements of trustworthiness were not different between patients and controls. There were no correlations between the primary measures of task performance and fasting oxytocin saliva concentrations. Conclusions. This is the first study to show that craniopharyngioma patients with hypothalamic lesions are impaired in some aspects of social cognition, which are of high relevance for everyday social interactions. These deficits suggest a disruption of the normal functionality of hypothalamic-fronto-limbic networks and/or additional areas of the social brain, which are at particular risk by hypothalamic location of the tumor and its treatment.